2007
DOI: 10.1186/1742-7622-4-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of personal digital assistants for data entry at the point of collection in a large household survey in southern Tanzania

Abstract: Background: Survey data are traditionally collected using pen-and-paper, with double data entry, comparison of entries and reconciliation of discrepancies before data cleaning can commence. We used Personal Digital Assistants (PDAs) for data entry at the point of collection, to save time and enhance the quality of data in a survey of over 21,000 scattered rural households in southern Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 2 publications
1
115
0
2
Order By: Relevance
“…In other evaluations, respondents tended to have accepted the new methods [8,23], but some concerns were raised over ‘outsider’ technology [4,14], and one study found a higher refusal rate with EDC [15]; the respondents we spoke to had no reservations regarding the technology. This acceptance in our setting may be due to the long-running nature of the project and good relationships with the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other evaluations, respondents tended to have accepted the new methods [8,23], but some concerns were raised over ‘outsider’ technology [4,14], and one study found a higher refusal rate with EDC [15]; the respondents we spoke to had no reservations regarding the technology. This acceptance in our setting may be due to the long-running nature of the project and good relationships with the community.…”
Section: Discussionmentioning
confidence: 99%
“…Other commentators also reported that users tended to prefer EDC over paper [813] and that interviewers without prior computing experience readily adapted to tablet use [2,8,23]. The experience has been less positive for data processing staff who feared for employment security, especially those without the higher level of skills and experience required to work on EDC.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to questions about the child's health, vaccination and IPTi status and any admissions, including those associated with a rash, were directly entered into personal digital assistants (PDA), as described previously. 25 These data were used to estimate the coverage of IPTi during 2007, powered to detect a coverage of 50% to within five percentage points, as well as the incidence of hospital admission with a rash as part of the safety evaluation.…”
Section: Rash-related Hospital Admissions In Children <2 Years Of Agementioning
confidence: 99%
“…The training lasted 2 weeks and consisted of detailed questionnaire review, case studies and a 3-day pilot survey. Work lists were produced from the cleaned census data, which had been collected using PDAs, 25 and provided to the VA interviewers within 4 weeks of the original household visit. The flow of VA questionnaires and job lists between the data unit and field was managed by the VA team supervisor whose responsibility it was to conduct quality control checks.…”
Section: Rash-related Deaths In Children Aged 2-11 Monthsmentioning
confidence: 99%
“…In 1991, Forster et al [15] in the Gambia were among the first to apply digital survey methods. They reported a 31% shorter enumeration time using electronic compared with paper questionnaires, and later in Tanzania, in 2005, a personal digital assistant (PDA) model of electronic devices was shown to achieve over 99% data completeness in a cross-sectional survey of over 21,000 rural households in southern Tanzania [16]. Initial analyses were possible within 24 hours after the last day of the survey, and there were no noteworthy experiences of device-related problems or data loss.…”
Section: Introductionmentioning
confidence: 99%